2010
DOI: 10.1097/ccm.0b013e3181eb9d0b
|View full text |Cite
|
Sign up to set email alerts
|

High-frequency percussive ventilation and low tidal volume ventilation in burns: A randomized controlled trial*

Abstract: A high-frequency percussive ventilation-based strategy resulted in similar clinical outcomes when compared with a low-tidal volume ventilation-based strategy in burn patients with respiratory failure. However, the low-tidal volume ventilation strategy failed to achieve ventilation and oxygenation goals in a higher percentage necessitating rescue ventilation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(73 citation statements)
references
References 37 publications
0
72
0
1
Order By: Relevance
“…[41][42][43] Th eoretically, APRV should minimize the primary physiologic mechanisms of VILI by maintaining an "open lung, " resulting in homogeneous lung ventilation. In addition, APRV gradually infl ates or "nudges" the lung open, which minimizes the tissue damage associated with aggressive recruitment maneuvers.…”
Section: Airway Pressure Release Ventilationmentioning
confidence: 99%
“…[41][42][43] Th eoretically, APRV should minimize the primary physiologic mechanisms of VILI by maintaining an "open lung, " resulting in homogeneous lung ventilation. In addition, APRV gradually infl ates or "nudges" the lung open, which minimizes the tissue damage associated with aggressive recruitment maneuvers.…”
Section: Airway Pressure Release Ventilationmentioning
confidence: 99%
“…IPV may be delivered via a face mask, a mouthpiece, an endotracheal tube, or a tracheostomy. Recent reports have suggested that IPV facilitates airway clearance and improves homogeneity of ventilation in patients with cystic fibrosis, [1][2][3][4][5] in patients with neuromuscular disorders with retention of mucus, 6,7 in patients with atelectasis, 8 -10 in burned patients with inhalation injury, [11][12][13] and in patients with COPD. 14 -17 Despite potential benefits related to the use of IPV therapy, the impact of setting parameters such as the ratio of inspiratory to expiratory time, the pressure, and the frequency on the mechanical effects produced by IPV devices is totally unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the theoretical advantages of IPV for enhanced secretion clearance, and the positive results of the aforementioned studies, another randomized trial comparing IPV to either conventional or lung-protective ventilation did not find significant differences in infectious complications, at least in patients with thermal injuries. 19 However, secretion clearance was neither monitored nor an end point in these studies.…”
Section: Intrapulmonary Percussive Ventilationmentioning
confidence: 99%